Morphological and molecular identification of a new species of Truncospora (Polyporales, Basidiomycota) in North America - Zhao, Chang-Lin; Xu, Feng; Pfister, Donald H. (Phytotaxa, 2016)
Truncospora wisconsinensis sp. nov., a new poroid wood-inhabiting species, is proposed based on a combination of molecular and morphological data. This species demonstrates a unique combination of characters including: annual habit; pileate basidiomata with a white pileus and pore surface; a dimitic hyphal system with non- to slightly dextrinoid, cyanophilous skeletal hyphae; and ellipsoid, truncate, slightly thick-walled, strongly dextrinoid basidiospores. Phylogenetic analyses using ITS and partial tef1-α support the position of this new species as a sister clade of T. ohiensis.